Shoulder Rotation Range of Motion and Serve Speed in Adolescent Male Volleyball Athletes: A Cross-Sectional Study - Rafael Telles; Ronaldo Alves Cunha; André Lima Yoshimura; Alberto Castro Pochini; Benno Ejnisman; Renato Rozenblit Soliaman (International Journal of Sports Physical Therapy)
# Background